2021
DOI: 10.1186/s12879-021-06476-y
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 inpatients with gastrointestinal onset: sex and care needs’ differences in the district of Ferrara, Italy

Abstract: Background COVID-19 is characterized by interstitial pneumonia, but a presentation of the disease with digestive symptoms only may occur. This work was aimed at evaluating: (1) the prevalence of presentation with digestive symptoms only in our cohort of COVID-19 inpatients; (2) differences between patients with and without gastrointestinal onset; (3) differences among males and females with gastrointestinal presentation; (4) outcomes of the groups of subjects with and without ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 29 publications
2
4
1
Order By: Relevance
“…In consistent with the published literature [7,24], no significant difference was detected in the mean level of transaminases among patients with and without digestive symptoms. In contrast, a meta-analysis by Wijarnpreecha et al [33] and a cross-sectional study by Teima et al [25] showed a higher level of transaminases in patients with GI symptoms.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In consistent with the published literature [7,24], no significant difference was detected in the mean level of transaminases among patients with and without digestive symptoms. In contrast, a meta-analysis by Wijarnpreecha et al [33] and a cross-sectional study by Teima et al [25] showed a higher level of transaminases in patients with GI symptoms.…”
Section: Discussionsupporting
confidence: 92%
“…Within our cohort, 104 (34.7%) patients presented with GI symptoms which is lower than the results reported by other studies conducted in the USA and China which were in the range of 50.5-61.3% [10,12]. In contrast, this prevalence was higher than other studies conducted in China, Italy, and Egypt [7,22,24,25].…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…Several studies have found that SARS-CoV-2 RNA can be found in stool in approximately 50% of patients with active infection [ 11 ], indicating the presence of viral infection along the GI tract. The local presence of SARS-CoV-2 along the GI tract is associated with greater intestinal inflammation and the release of cytokines such as interleukin-6 (IL-6) and Tumor Necrosis Factor-α [ 12 ]. These cytokines play an important role in causing the local and systemic inflammatory response and are released in response to tissue injury and pro-inflammatory stimulus from the innate and adaptive immune system.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Greco and colleagues looked at the distribution of symptoms depending on age, sex, and disease outcome, among other factors. In this study, gastrointestinal symptoms occurred in 12.5% of infected individuals [ 34 ].…”
Section: Introductionmentioning
confidence: 99%